2013
DOI: 10.3329/jdnmch.v18i2.16022
|View full text |Cite
|
Sign up to set email alerts
|

Status of Serum bilirubin, Serum Proteins and Prothrombin time in babies with Perinatal Asphyxia

Abstract: Abstract:Background and Objectives: Because of hypoxemia, different organ systems of the body are affected in perinatal asphyxia. This study was carried out to see the status of Serum bilirubin, Serum Proteins and Prothrombin time in asphyxiated babies and to know any correlation existing between hepatic dysfunction and the severity of perinatal asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
4
1
Order By: Relevance
“…Islam et al, and contradicted by some like the Elsadek et al, study, where they found no significant correlation between serum level of ALP and stages of HIE [9][10][11]. In our study, we have shown that how mortality is increased from lower to higher HIE stages (nil in HIE I to 29.42% in HIE III).…”
contrasting
confidence: 78%
“…Islam et al, and contradicted by some like the Elsadek et al, study, where they found no significant correlation between serum level of ALP and stages of HIE [9][10][11]. In our study, we have shown that how mortality is increased from lower to higher HIE stages (nil in HIE I to 29.42% in HIE III).…”
contrasting
confidence: 78%
“…This might be due to the fact that asphyxia is an insult to the newborn due to lack of oxygen, lack of perfusion to various organs which results in multiorgan system dysfunction due to hypoxic damage mainly on brain, lung, liver and intraventricular haemorrhage which affect the bilirubin conjugation ability of the liver that results in jaundice. 41 Also, perinatal asphyxia with hypoxic-ischaemic encephalopathy can lead to disruption of the blood-brain barrier, thereby allowing free entry of the unconjugated bilirubin to the neurons resulting in acute bilirubin encephalopathy. Besides, kidney damage from PNA can lead to less excretion of the conjugated bilirubin, thereby causing conjugated hyperbilirubinaemia and jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopia [48] supported that neonatal jaundice is in uenced by birth asphyxia. This similarity in nding was because perinatal asphyxia remains a common problem in the neonatal nursery and is a signi cant coincidence with neonatal hyperbilirubinemia in neonatal intensive care and it was also an insult to the newborn due to lack of oxygen, lack of perfusion to various organs which ends up in multi-organ system dysfunction due to hypoxic damage principally on brain, lung, liver and intraventricular hemorrhage that affect bilirubin conjugation ability of the liver that leads to jaundice [49]. Also, perinatal asphyxia with the hypoxic-ischemic neurological disorder will disrupt the blood-brain barrier, thereby permitting free entry of the unconjugated bilirubin to the neurons leading to a neurological disorder.…”
Section: Discussionmentioning
confidence: 99%